Sturdy for common things: cultivating moral sensemaking on the front lines of practice. Issue 4 (21st November 2011) - Browning, David M
Abstract : This essay argues that the field of bioethics should concern itself especially with the process of making moral sense that unfolds among clinicians, patients and family members during common but high-stakes conversations occurring on the front lines of practice. The essay outlines the parameters of a bioethics grounded in the moral experience of patients, families and practitioners. It challenges ethicists, educators, and clinician leaders to commit themselves to advocating and developing creative approaches to learning that will cultivate the moral sensibilities of frontline clinicians in this critically important domain of practice.